Career Adaptability and Career Construction as Mediating Variables Between Hardiness and Vocational Identity - Enrique Merino-Tejedor; María José Serrano-Fernández; Maria Boada-Cuerva; Beatriz Sora (International Journal for Research in Vocational Education and Training)
Background: The Career Construction Theory (CCT) focuses on the active role people can play when they create and design their singular paths for career success. Unlike other career guidance theories that focus their attention on identifying vocational interests or on the fit between the person and the work settings, CCT raises the possibility that people can go beyond the determinants of their life. This study tested the adaptation model proposed by Career Construction Theory. Consolidation of vocational identity is particularly important at the university stage, in which people decide their first steps about their professional future.